Discretization of a mathematical model for image analysis based on the optics of spiral beams - S.A. Kishkin; S.P. Kotova (Компьютерная оптика)
The article briefly outlines a mathematical model for recognizing contours of the objects of interest in a raster image. The process of its discretization is discussed in more detail as part of the development of numerical methods that allow the proposed model to be implemented using modern computer technology, while achieving real-time performance. Explicit mathematical procedures suitable for writing application software codes are given, an estimate of computational complexity is obtained, and the possibility of achieving real-time performance is confirmed. Results of a numerical experiment on the reconstruction of spiral light beams are presented.